Valores de referência para cobre e zinco no plasma e no eritrócito em adultos universitários na cidade de Natal-RN - Nascimento, Débora Azevedo do (2006)
This study aimed builds reference values for copper and zinc, of healthy adults in Natal-RN, and to identify the influence of the gender, age, body mass index (BMI) and diet, on those values. They were assessed 123 healthy students of the Universidade Federal do Rio Grande do Norte (UFRN), both genders, with age between 19 and 41 years. The project was approved by the Ethics Committee in Research of UFRN. BMI was determined and the food consume was accomplished through a 24h recordatory. Dietary was evaluated as the energy, macronutrients, copper and zinc, according to the recommendations of National Academy of Sciences (2001; 2002). Analyses of the copper and zinc concentrations in the plasma and erythrocytes were accomplished by flame atomic absorption spectrometry. The casuistic came quite homogeneous as for the distribution for gender and age, being the largest number of individuals between the 19 and 24 years old. Most of the volunteers presented anthropometric nutritional state inside of the normality patterns. Chronic diseases family antecedents and sedentarysm were observed. Diet was characterized with low consumption of zinc, appropriate of copper and of lipids. Average concentrations of plasma copper (p=0,002), erythrocyte copper (μg/dL, p=0,036; μg/gHb, p=0,038), and plasma zinc (p=0,022) were different among the genders, what was demonstrated by the largest values of copper in the female gender and larger of zinc in the masculine. Plasma copper values still suffered interference of the variables: energy, carbohydrate and copper consumption, all classified in agreement with the median, besides the protein classified according to the percentage contribution for the dietary total energy. The study allowed to establish reference values for erythrocyte zinc (1.261,6-1.344,0 μg/dL e 51,0-54,3 μg/gHb) and to suggest "indicative" of reference values for plasma (108,4 130,2 μg/dL) and erythrocyte (female = 85,0 91,4 μg/dL; masculine = 80,2 86,5 μg/dL) copper and plasma zinc (female = 98,8 105,8 μg/dL; masculine = 104,6 111,6 μg/dL)